The use of the blood lactate curve to develop training intensity guidelines for the sports of track and field and cross-country - Belcher, C. P.; Pemberton, C. L. (International Journal of Exercise Science, 2012)
The purpose of this study was to develop and field test a standardized system of training intensity guidelines for the sport of track and field/cross country, modeled after the standardized system of training intensity guidelines developed, adopted, and in use by U.S.A. Swimming. This study was quantitative and focused on the development and field-testing of standardized training intensity guidelines, based on the blood lactate curve and energy metabolism. The findings showed that as intensity increased so did participants` blood lactate concentration, heart rate, and ratings of perceived exertion. A Pearson product-moment correlation analysis between the mean values of blood lactate concentration, heart rate, and ratings of perceived exertion, and the corresponding training intensity ranges revealed significant positive correlations between mean blood lactate values (r = 0.99, p 0.05), as were heart rate and ratings of perceived exertion (r =0.96, p <0.005). Measures of blood lactate were positively and significantly correlated to ratings of perceived exertion (r =0.82, p <0.05). These findings validated the training intensity guidelines model.